Efficacy of hemostasis by gastroduodenal covered metal stent placement for hemorrhagic duodenal stenosis due to pancreatobiliary cancer invasion: a retrospective study - Yasunari Sakamoto; Taku Sakamoto; Akihiro Ohba; Mitsuhito Sasaki; Shunsuke Kondo; Chigusa Morizane; Hideki Ueno; Yutaka Saito; Yasuaki Arai; Takuji Okusaka (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims Advanced pancreatic and biliary tract cancers can invade the duodenum and cause duodenal hemorrhagic stenosis. This study aimed to evaluate the efficacy of covered self-expandable metal stents in the treatment of cancer-related duodenal hemorrhage with stenosis. Methods Between January 2014 and December 2016, metal stents were placed in 51 patients with duodenal stenosis. Among these patients, a self-expandable covered metal stent was endoscopically placed in 10 patients with hemorrhagic duodenal stenosis caused by pancreatobiliary cancer progression. We retrospectively analyzed the therapeutic efficacy of the stents by evaluating the technical and clinical success rates based on successful stent placement, degree of oral intake, hemostasis, stent patency, and overall survival. Results The technical and clinical success rates were 100%. All 10 patients achieved a gastric outlet obstruction scoring system score of three within two weeks after the procedure and had no recurrence of melena. The median stent patency duration and overall survival after stent placement were 52 days (range, 20-220 days) and 66.5 days (range, 31-220 days), respectively. Conclusions Endoscopic placement of a covered metal stent for hemorrhagic duodenal stenosis associated with pancreatic or biliary tract cancer resulted in duodenal hemostasis, recanalization, and improved quality of life.